2013
DOI: 10.1002/2013gl058294
|View full text |Cite
|
Sign up to set email alerts
|

Formation of sprite streamers at subbreakdown conditions from ionospheric inhomogeneities resembling observed sprite halo structures

Abstract: [1] Modeling results of sprite streamer formation from large ionospheric inhomogeneities or patches (several tens to hundreds of meter wide) indicate that positive streamers can be initiated at subbreakdown conditions from the inhomogeneities with a density comparable to sprite halo densities. For spherical patches with a given radius, the minimum density required for streamer initiation decreases with increasing ambient field. For a given density, the minimum size of the inhomogeneity decreases with increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…The average speed is 3 Â 10 6 m s À 1 , and the streamer channel density is about 8 Â 10 10 m À 3 . The head field, channel density, speed and acceleration of the streamer are consistent with previous streamer modelling results 10,15,16,21,22,25 .…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The average speed is 3 Â 10 6 m s À 1 , and the streamer channel density is about 8 Â 10 10 m À 3 . The head field, channel density, speed and acceleration of the streamer are consistent with previous streamer modelling results 10,15,16,21,22,25 .…”
Section: Resultssupporting
confidence: 89%
“…The propagation characteristics of a single sprite streamer, such as acceleration, expansion and brightening, are relatively well understood [10][11][12][13][14][15][16][17][18] . However, how sprite streamers are initiated, a critical question to understand the responses of the upper atmosphere to sudden, strong QE field impacts, is still under active debate 14,[19][20][21][22][23][24][25][26] .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies by Kosar et al (2012) showed that when an appropriate ionization column is introduced, the streamer could be initiated in a variety of electric fields with the lowest electric field of 0.3 E k (E k is the breakdown threshold field). Kosar et al (2013) further indicated that positive streamers can be initiated at subbreakdown conditions from the inhomogeneities with a density comparable to sprite halo densities, also showing the importance of inhomogeneities in sprite initiation. These results show that except for the CMC value of the lightning there are also other factors that play roles in sprite initiation.…”
Section: Discussionmentioning
confidence: 85%